Chromatic dispersion-tolerant mode-locking of directly synthesized graphene for the control of laser pulse energy - Didychenko, Denys; Oleksiy, Kovalchuk; Uddin, Siam; See, Sungjae; Song, Yong-Won (Elsevier BV, 2024)
Transfer-free direct synthesis of graphene (Gf) has been anticipated to develop small-footprint ultrafast optical devices that rely on the excellent nonlinearity of defect-suppressed Gf. Atomic carbon spraying (ACS) technique enables a direct and conformal growth of 3-dimensional (3D) Gf on the 3D surface of substrates by introducing a new ceramic catalyst. However, with the high density of grain boundaries retained in the resultant Gf nanocrystals, their unimpaired optical nonlinearity should be verified. We demonstrate a fiber ring femtosecond laser based on passive mode-locking of the ACS Gf synthesized on the side-polished surface of an optical fiber for the asymmetric nonlinear interaction of laser evanescent field and Gf. Widely operable chromatic dispersion range for the ACS Gf-based mode-locking is shown experimentally to tune the individual pulse energy. The ACS Gf manages a reliable interplay between the anomalous dispersion and optical nonlinearity of the laser cavity at high-intracavity power, resulting in dispersion-tolerant short pulse generation. Output pulse energy up to 9.05 nJ of the hyperbolic secant pulses is achieved with the extra-length of single mode fibers ranging from 30 to 250 m, ensuring the robust nonlinear operation of the ACS Gf.